Enhancing Development Assistance to Africa : Lessons from Scaling-Up Scenarios - Gaertner, Matthew (Departmental Papers; Departmental Paper, 2012)
The pace of progress toward achievement of the Millenium Development Goals (MDG) in many sub-Saharan African countries remains too slow to reach targets by 2015, despite significant progress in the late 1990s. The MDG Africa Steering Group, convened in September 2007 by the UN Secretary-General, designated 10 countries for pilot studies to investigate how existing national development plans would be impacted by scaled up development aid to Africa. This joint publication of the IMF and the United Nations Development Programme reports conclusions drawn from these pilot studies and summarizes country-specific results for Benin, the Central African Republic, Ghana, Liberia, Niger, Rwanda, Tanzania, Togo, Sierra Leone, and Zambia.